Diels–Alder type adducts with potent alpha-glucosidase inhibitory activity from Morus macroura. (August 2018) - Wang, Yi-Fan; Yu, Mei-Hua; Xu, Liang-Jin; Niu, Li-Xin; Huang, Chun-Yue; Xu, Hui; Yang, Pei-Ming; Hu, Xiao
Graphical abstract: Highlights: Two new bridged-ring type Diels–Alder adducts were isolated from M. macroura . Three types of Diels–Alder adducts illustrate the chemodiversity of M. macroura . Compounds 1–9 showed potent α-glucosidase inhibitory activity. Abstract: Two new Diels–Alder type adducts, macrourins I and J (1–2 ), along with seven known analogues (3–9) were isolated from the stems of Morus macroura Miq. The structures of the two new compounds were elucidated by extensive analysis of spectroscopic data. Compounds 1–9 all showed highly potent in vitro α-glucosidase inhibitory activities, and the IC50 values of compounds 1 and 2 were 1.70 and 1.58 μM, respectively, approximately 800 times stronger than the positive control, acarbose.